2018
DOI: 10.1016/j.celrep.2018.04.102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Drivers of Aneuploidy in Breast Tumors

Abstract: SUMMARY Although aneuploidy is found in the majority of tumors, the degree of aneuploidy varies widely. It is unclear how cancer cells become aneuploid or how highly aneuploid tumors are different from those of more normal ploidy. We developed a simple computational method that measures the degree of aneuploidy or structural rearrangements of large chromosome regions of 522 human breast tumors from The Cancer Genome Atlas (TCGA). Highly aneuploid tumors overexpress activators of mitotic transcription and the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 50 publications
5
57
0
Order By: Relevance
“…Our results revealed a group of "accelerator" transcriptional factors, such as E2F7 and E2F8, can activate the genes associated with HRD as well as a series of genes involved in the cell cycle and proliferation. The overexpression E2F7 have been reported to result in an increase of aneuploidy in breast cancer cells (18). On the contrary, another group of "stabilizer" transcriptional factors, such as RFX2 and NFYA, can activate a number of CT genes to promise the timely repair of double-strand breaks in the late meiosis stages, but these CT genes were not co-activated with HRD related CT genes in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Our results revealed a group of "accelerator" transcriptional factors, such as E2F7 and E2F8, can activate the genes associated with HRD as well as a series of genes involved in the cell cycle and proliferation. The overexpression E2F7 have been reported to result in an increase of aneuploidy in breast cancer cells (18). On the contrary, another group of "stabilizer" transcriptional factors, such as RFX2 and NFYA, can activate a number of CT genes to promise the timely repair of double-strand breaks in the late meiosis stages, but these CT genes were not co-activated with HRD related CT genes in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…In recent studies, decreased levels of FOXM1 was shown to cause mitotic decline, genomic instability, and senescence during human aging (Macedo et al, 2018). Conversely, FOXM1 overexpression was found to promote mitotic defects and genomic instability (Pfister et al, 2018). Together, these data suggest that tight regulation of FOXM1 expression and function are important for maintaining proper mitotic function and genomic stability.…”
Section: Hgsc Tissues and Cells Show Robust Overexpression Of Both Fomentioning
confidence: 90%
“…A recent analysis of highly aneuploidy breast cancers in TCGA found overexpression of three transcriptional regulators, E2F1, MYBL2, and FOXM1 [13]. Overexpression of these genes in nontransformed Xenopus embryos was sufficient to significantly increase the rate of chromosomal missegregation and initiate aneuploidy.…”
Section: Differentially Expressed Genes In Cin-mentioning
confidence: 99%